Author’s Index - Sorooshian, Shahryar (Hungarian Communication Studies Association, 2017)
This letter presents a new mathematical index (Author’s index; A index) for comparison of authors/scholars. The index was a medal winner in ISEBA 2017; an annual international exhibition and competition for social sciences innovation in Malaysia